Respuesta :
2(x + 2) + 2 = 2(x + 3) + 1
2x + 4 + 2 = 2x + 6 + 1
2x + 6 = 2x + 7 - NO SOLUTION
(subtract 2x from both sides, then 6 = 7 FALSE)
2x + 3(x + 5) = 5(x – 3)
2x + 3x + 15 = 5x - 15
5x + 15 = 5x - 15 - NO SOLUTION
4(x + 3) = x + 12
4x + 12 = x + 12 - ONE SOLUTION
4 – (2x + 5) = (–4x – 2)
4 - 2x - 5 = -4x - 2
-2x - 1 = -4x - 2 - ONE SOLUTION
5(x + 4) – x = 4(x + 5) – 1
5x + 20 - x = 4x + 20 - 1
4x + 20 = 4x + 19 - NO SOLUTION
2x + 4 + 2 = 2x + 6 + 1
2x + 6 = 2x + 7 - NO SOLUTION
(subtract 2x from both sides, then 6 = 7 FALSE)
2x + 3(x + 5) = 5(x – 3)
2x + 3x + 15 = 5x - 15
5x + 15 = 5x - 15 - NO SOLUTION
4(x + 3) = x + 12
4x + 12 = x + 12 - ONE SOLUTION
4 – (2x + 5) = (–4x – 2)
4 - 2x - 5 = -4x - 2
-2x - 1 = -4x - 2 - ONE SOLUTION
5(x + 4) – x = 4(x + 5) – 1
5x + 20 - x = 4x + 20 - 1
4x + 20 = 4x + 19 - NO SOLUTION
Equations one, two, and the froth equation have no solution.
has no soltion 2(x + 2) + 2 = 2(x + 3) + 1
2x + 4 + 2 = 2x + 6 + 1
2x + 6 = 2x + 7
It has no solution
(subtract 2x from both sides, then 6 = 7 FALSE)
When an equation has no solution?
The constants are the numbers alone with no variables. If the coefficients are the same on both sides then the sides will not equal, therefore no solutions will occur.
2x + 3(x + 5) = 5(x – 3)
2x + 3x + 15 = 5x - 15
5x + 15 = 5x - 15
It has no solution.
4(x + 3) = x + 12
4x + 12 = x + 12
Therefore this equation has one solution.
4 – (2x + 5) = (–4x – 2)
4 - 2x - 5 = -4x - 2
-2x - 1 = -4x - 2
Therefore this equation has one solution
5(x + 4) – x = 4(x + 5) – 1
5x + 20 - x = 4x + 20 - 1
4x + 20 = 4x + 19 -
It has no solution.
Equations one, two, and the froth equation have no solution.
To learn more about the solution of the equation visit:
https://brainly.com/question/2972832
#SPJ2